A rare case of double orifice mitral valve with perimembranous ventricular septal defect: Application of three-dimensional echocardiography for clinical decision making - Tandon Rohit; Takkar Shibba; Kumbhkarni Shailender; Kumar Naveen; Aslam Naved; Mohan Bishav; Wander G (Wolters Kluwer Medknow Publications, 2010)
Double orifice mitral valve (DOMV) is an uncommon anomaly of surgical importance characterized by a mitral valve with a single fibrous annulus with two orifices opening into the left ventricle (LV). Subvalvular structures, especially the tensor apparatus, invariably show various degrees of abnormality. Associated congenital heart defects are common, though DOMV can occur as an isolated anomaly. Two-dimensional echocardiography is useful for diagnosis but combining it with real-time three-dimensional echocardiography helps in a more detailed evaluation of mitral valve and subvalvular structures as is shown in this case description.